(untitled) (The Journal of Interdisciplinary Human Studies, 2026)
This scholarly article provides an in-depth analysis of the main theoretical and conceptual approaches to studying the refugee issue within the system of international relations. The article highlights the close interconnection between forced migration processes and global politics, security, state sovereignty, human rights, and international institutions. It also analyzes scholarly views on the refugee issue within the frameworks of realism, liberal institutionalism, constructivism, securitization, and normative-critical approaches, and reveals the place of this problem in contemporary world politics.